PENGARUH KOMBINASI TAKARAN PUPUK NITROGEN DAN PUPUK ORGANIK GRANULAR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CAISIM (Brassica parachinensis Bailey) KULTIVAR PAKCHOY - Supriatna Supriatna; A Harijanto; Tety Sucianti (Agroswagati Jurnal Agronomi, 2017)
This study aims to determine the effect of Combination of Nitrogen Fertilizer and Granular Organic Fertilizer on the Growth and Yield of Caisim (Brassica chinensis Bailey) Cultivator Pak Choy. The experiment was carried out on the experimental site of the Cigugur Fisheries and Forestry Extension Center (BP3K) in Cisantana Village, Cigugur Subdistrict, Kuningan Regency, West Java Province. Land in the experiment area includes latosol soil type, rainfall including medium type (D), and height of 700 meters above sea level (asl). The time of the research was conducted from September to October 2012.The experimental method used was using the experimental method with factorial randomized block design (RBD), consisting of 16 combinations, namely treatment A (nitrogen 45 kg / ha, 0 kg POG / ha), B (nitrogen 90 kg / ha, 0 kg POG / ha), C (nitrogen 135 kg / ha, 0 kg POG / ha), D (nitrogen 180 kg / ha, 0 kg POG / ha), E (nitrogen 45 kg / ha, 425 kg POG / ha), F (90 kg nitrogen / ha, 425 kg POG / ha), G (135 kg nitrogen / ha, 425 kg POG / ha), H (180 kg nitrogen / ha, 425 kg POG / ha), I (45 kg nitrogen / ha, 850 kg POG / ha), J (nitrogen 90 kg / ha, 850 kg POG / ha), K (nitrogen 135 kg / ha, 850 kg POG / ha), L (nitrogen 180 kg / ha, 850 kg POG / ha), M (45 kg nitrogen / ha, 1275 kg POG / ha), N (90 kg nitrogen / ha, 1275 kg POG / ha), O (nitrogen 135 kg / ha, 1275 kg POG / ha), P (180 kg nitrogen / ha, 1275 kg POG / ha). Each treatment was repeated 2 times, so 32 trial plots were obtained.The variables observed were plant height, number of leaves, gross weight per plant, gross weight per plot, net weight per plant, and net weight per plot. The results showed a significant effect of the dose of nitrogen fertilizer and granular organic fertilizer on plant age of 30 HST, number of leaves aged 10 and 30 HST, gross weight per plot, and net weight per plot. The dose of nitrogen fertilizer 90 kg / ha and granular organic fertilizer 850 kg / ha shows the best influence on net weight per plot which produces production of 20.70 kg / plot or equivalent to 82 tons / ha.